CFD and 1D simulation of transient flow effect on air vessel (2018)
The estimation of unsteady parameters in two-phase condition is crucial for the safety and reliability of the hydraulic systems. There are plenty of one-dimensional (1D) simulation tools for unsteady flow estimation being some of them able to present good results in monophasic flows, while almost all of them are not suitable for two-phase flows. In this research, an experimental apparatus including valves, pipes and an air vessel is used to fulfil the experiments. A mathematical formulation and a two-dimensional computational fluid dynamics (2D CFD) model have been used to predict the extreme conditions. Results show that 1D model is able to predict pressure values with acceptable accuracy. However, the 2D CFD model can be used to detect the specialized problems in a system by providing very high range of the information. © BHR Group 2018 Pressure Surges 13